Characterization and Study of Gene Expression Profiles of Human Periodontal Mesenchymal Stem Cells in Spheroid Cultures by Transcriptome Analysis. (19th October 2021) - Suga, Takenori; Usui, Michihiko; Onizuka, Satoru; Sano, Kotaro; Sato, Tsuyoshi; Nakazawa, Kohji; Ariyoshi, Wataru; Nishihara, Tatsuji; Nakashima, Keisuke
Abstract : A spheroid is known as a three-dimensional culture model, which better simulates the physiological conditions of stem cells. This study is aimed at identifying genes specifically expressed in spheroid-cultured human periodontal ligament mesenchymal stem cells (hPDLMSCs) using RNA-seq analysis to evaluate their functions. Transcriptome analysis was performed using spheroid and monolayer cultures of hPDLMSCs from four patients. Cluster and Gene Ontology analyses revealed that genes involved in cell-cell adhesion as well as the G2/M and G1/S transitions of mitotic cell cycles were strongly expressed in the monolayer culture group. However, genes involved in the negative regulation of cell proliferation, histone deacetylation, and bone morphogenetic protein signaling were strongly expressed in the spheroid culture group. We focused on the transcription factor nuclear receptor subfamily 4 group A member 2 ( NR4A2 ) among the genes that were strongly expressed in the spheroid culture group and analyzed its function. To confirm the results of the transcriptome analysis, we performed real-time polymerase chain reaction and western blotting analyses. Interestingly, we found that the mRNA and protein expressions of NR4A2 were strongly expressed in the spheroid-cultured hPDLMSCs. Under osteogenic differentiation conditions, we used siRNA to knock down NR4A2 in spheroid-cultured hPDLMSCs to verify its role in osteogenesis. We found that NR4A2 knockdown significantly increased the levels of mRNA expression for osteogenesis-related genes alkaline phosphatase ( ALP ), Osteopontin ( OPN ), and type 1 collagen ( COL1 ) (Student's paired t -test, p < 0.05 ). ALP activity was also significantly increased when compared to the negative control group (Student's paired t -test, p < 0.05 ). Additionally, spheroid-cultured hPDLMSCs transfected with siNR4A2 were cultured for 12 days, resulting in the formation of significantly larger calcified nodules compared to the negative control group (Student's paired t -test, p < 0.05 ). On the other hand, NR4A2 knockdown in hPDLMSC spheroid did not affect the levels of chondrogenesis and adipogenesis-related genes under chondrogenic and adipogenic conditions. These results suggest that NR4A2 negatively regulates osteogenesis in the spheroid culture of hPDLMSCs.